Ai-Based Web Application Design For Photographic Image Quality Optimization Through Digital Image Filtering Method - Ibnu Pribudianto; Al-Khowarizmi (Tsabit Journal of Computer Science, 2025)
Image quality in photography is often disrupted by factors such as poor lighting or incorrect focus, resulting in blurry images. This study aims to enhance image sharpness using digital image filtering methods, namely Unsharp Masking, High-Pass Filtering, and Sobel Filter. These methods are tested to evaluate their effectiveness in clarifying image details. The study also develops a web-based application powered by AI to help users edit images without requiring technical skills. A quantitative experimental method with a descriptive approach is used, and evaluation is conducted using PSNR, SSIM, and user questionnaires. The results show that the application of sharpening methods can significantly improve the quality of photographic images, and integration into a web platform provides easy access for the general public. This application is expected to be a practical solution for photographers, editors, and general users to obtain high-quality images efficiently and quickly.